2005
DOI: 10.1097/01.mlr.0000163661.67170.b9
|View full text |Cite
|
Sign up to set email alerts
|

Staff Turnover and Quality of Care in Nursing Homes

Abstract: These findings are significant because the belief that staff turnover influences quality is pervasive. The cross-sectional results are only able to show associations, nonetheless, few empirical studies in the literature have shown this relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
283
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(288 citation statements)
references
References 35 publications
(64 reference statements)
4
283
1
Order By: Relevance
“…Family members often threaten legal action to get adequate care for their family members (Johnson, Dobalian, Burkhard, Hedgecock, & Harman, 2004). Staff are dissatisfied, and turnover is very high (Castle, 2005(Castle, , 2006. Long-term care institutions are plagued with challenges that may negatively affect residents' QoL, such as high staff turnover, rigid schedules, and routines that minimize personal choice.…”
Section: Introductionmentioning
confidence: 99%
“…Family members often threaten legal action to get adequate care for their family members (Johnson, Dobalian, Burkhard, Hedgecock, & Harman, 2004). Staff are dissatisfied, and turnover is very high (Castle, 2005(Castle, , 2006. Long-term care institutions are plagued with challenges that may negatively affect residents' QoL, such as high staff turnover, rigid schedules, and routines that minimize personal choice.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have asserted that nurse turnover in nursing homes are associated with lowquality care (Bostick et al 2006;Castle and Engberg 2005;Collier and Harrington 2008), although most studies find no statistically significant relationship and fail to account for the fact that nursing turnover is endogenous. In this paper, we use IV estimation to address the endogeneity of nurse turnover on mortality and quality of care.…”
Section: Resultsmentioning
confidence: 99%
“…While a few studies have found that higher nurse turnover can lead to worse quality, the vast majority of studies do not find a statistically significant relationship (Castle and Anderson 2011;Castle and Engberg 2005;Castle et al 2007;Lerner et al 2011;Thomas et al 2013). The lack of using causal identification by the current literature may explain why most studies find statistically insignificant effects.…”
Section: Conceptual Model Of Turnover and Nursing Home Qualitymentioning
confidence: 99%
“…There is some evidence supporting the potential importance of compensation for recruiting and retaining a stable workforce. With the low wages and benefits, nursing homes find it difficult to compete with fast-food restaurants and other low-wage service sectors and the turnover rates are high [63,126], which are associated with poor quality of care [123,[127][128][129]. Since AB1629 changed payment incentives to encourage and reward nursing homes to invest more in direct care labor, we expect to see nursing homes increasing staffing levels and/or wages.…”
Section: Nursing Home's Investment In Labormentioning
confidence: 99%